Participation of local companies in electronic public procurement: A study of the municipality of Laranjal/PR (International Seven Journal of Multidisciplinary, 2023)
The present work is a case study of the municipality of Laranjal Pr, which shows how local companies are participating in electronic auctions covering the periods from 2019 to 2023. Using information from the municipality of Laranjal website at www.laranjal.pr. gov.br/licitação/pregãoeletronico, accessible means such as electronic media and physical processes containing the minutes of bidding processes that have already taken place in the municipality developed by the BLL and Licitar Digital bidding platforms with accurate reports for research use. With the beginning of the electronic auction in the Municipality of Laranjal Pr in 2019, no local company participated, on the one hand because it was not suitable for electronic functionality and on the other because it was a more specific object, making it not possible for them to participate. , and for this type of object the municipality does not have a company with the capacity and structure to meet this demand. From the year 2020 onwards, with the platform's announcements, interest began to appear on the part of some local companies, only one that participated and was also the winner, from the year 2021 onwards there has been a greater number of companies and so on. the following years, with an increase in the participation of local companies each year, thus we can observe that local companies are adapting to enter the market to be suppliers of products or services in public purchases in the municipality of Laranjal Pr, with an increase gradual annually, it is concluded that for next year a greater number of participants and local winners in the bids are expected.